Teaching queer literature to foster gender diversity awareness - Richard M. Bañez; Aimee M. Guia (Institute of Advanced Engineering and Science, 2026)
This qualitative study explores how literature educators in higher education design and implement pedagogical practices for teaching queer literature to foster gender diversity awareness in a Philippine state university context. Drawing on focus group discussions (FGDs) with 22 educators across multiple campuses, guided by data saturation and reflexive practices, the study identifies a framework comprising four interrelated domains: literary selection, teaching model integration, learning activities, and assessment strategies. Educators purposefully select authentic and culturally relevant queer texts, employ integrative language, cultural, and personal growth models, and design aesthetic, analytical, and reflective learning tasks that engage students cognitively, affectively, and performatively. Teaching through this framework supports students’ critical interrogation of norms, reflexive meaning-making, and negotiation of identity and difference, operationalizing queer theoretical concepts such as heteronormativity, performativity, and power dynamics. The study advances queer pedagogy by positioning literature as a transformative mechanism for critical consciousness, inclusivity, and identity awareness. Implications are discussed for curriculum design, teacher education, and inclusive policy in culturally conservative contexts.